The Effect of Social Media and Service Quality on Patient Loyalty with Satisfaction as Mediation at Mojosongo Clinic 1 - Setia Budi, Rahmad; Purwo Saputro, Edy; Alam R, Yusuf (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Mojosongo 1 Clinic is a health clinic that was established in 2017. The clinic has a busy situation every day. This is a reference for researchers to find out whether social media factors and customer quality can affect customer loyalty. The clinic has social media accounts in the form of Instagram and WhatsApp to carry out marketing through social media. The use of social media as a marketing tool has been used for 6 years. The purpose of this study is to analyze the effect of social media and service quality on patient loyalty with satisfaction as mediation at Mojosongo 1 Clinic. This research is quantitative. The participants in this study were visitors to Mojosongo 1 Health Centre. Purposive sampling is the sampling method used. The calculation uses Ferdinand's idea. 140 respondents were obtained as the research sample. Primary data was used in making this research. Questionnaire distribution is the data collection method in this study. The data analysis method in this study uses SMARTPLS software, namely Partial Least Square (PLS). The results of this study show that social media has a positive and significant impact on Loyalty. Service quality has a negative and insignificant impact on Loyalty. Social Media and service quality have a positive and significant impact on Satisfaction. Satisfaction has a positive and significant impact on Loyalty. Social Media has a positive and significant impact on Loyalty through Satisfaction. Service quality has a positive and significant impact on Loyalty through Satisfaction.